Five years sharing optometry with a global and multidisciplinary audience - González-Méijome, José Manuel (2013)
[Excerpt] The clinical and scientific activity in the field of optometry has experienced a rapid expansion in the last decades.1 In many places around the World, where this specialty was not developed in the middle of the 20th century, Optometry is now flourishing with new schools, training centers and other structures. This made possible to provide eye care to millions of people who otherwise would not be served. These strategies have been particularly important in Asia, Middle East, Africa and Latin America. Besides the publication of mainstream state of the art research results in the field of optometry and visual sciences,2, 3, 4 the Journal of Optometry has been committed to be a platform for sharing with a Global Audience the scientific and clinical information coming from or related with developing countries in those areas. The issue being published now is a good example, with a significant proportion of its information arising directly or indirectly from populations whose ocular characteristics and ocular morbidity are now better known. [...]